Impact of high magnification sperm selection on neonatal outcomes: a retrospective study - Gaspard, Olivier; Vanderzwalmen, Pierre; Wirleitner, Barbara; Ravet, Stéphanie; Wenders, Frédéric; Eichel, Verena; Mocková, Alice; Spitzer, Dietmar; Jouan, Caroline; Gridelet, Virginie; Martens, Henri; Henry, Laurie; et al. (Journal of assisted reproduction and genetics, 2018)
PURPOSE: The aim of this study was to compare the effect of the deselection of spermatozoa presenting vacuole-like structures using IMSI (intracytoplasmic morphologically selected sperm injection) with ICSI (intracytoplasmic sperm injection) by means of neonatal outcomes. METHODS: In a retrospective two-center analysis, a total of 848 successful IMSI or ICSI cycles ending with a live birth, induced abortion, or intrauterine fetal death (IUFD) were included. RESULTS: The IMSI and ICSI groups included 332 and 655 babies or fetuses, respectively. The parents were older in the IMSI group than in the ICSI group (mothers were 35.1 vs 32.9 years, and fathers were 39.1 vs 36.2 years). The multiple pregnancy rate was higher in the IMSI group. The mean pregnancy duration and mean birth weight were almost identical in both groups. There was no significant difference in major congenital malformations between the two groups. However, this rate was decreased in the IMSI group compared to that in the ICSI group (1.8 vs 3.2%), the difference being mainly found in singletons (1.4 vs 3.3%). Boys were more often affected than girls in both groups. The percentages of chromosomal abnormalities did not differ between the IMSI and ICSI groups (0.6 and 0.8%). The reported congenital malformations mainly affected the heart, urogenital, and musculoskeletal systems. CONCLUSIONS: In the present study, the malformation rates observed in the IMSI and ICSI groups were not significantly different, even if slightly lower after IMSI. However, the observed difference followed the same trends observed in previous reports, indicating the possible impact of IMSI on decreasing congenital malformation occurrences. This highlights the necessity to prospectively evaluate the impact of IMSI on neonatal outcome after IVF treatment.
Keywords: dospělí; Pregnancy Outcome; těhotenství; výsledek těhotenství; retrospektivní studie; Humans; Spermatozoa; Infertility, Male; úhrn těhotenství na počet žen v reprodukčním věku; Embryo Transfer; mužské pohlaví; Adult; Pregnancy Rate; přenos embrya; ženské pohlaví; mužská infertilita; Sperm Injections, Intracytoplasmic; intracytoplazmatické injekce spermie; lidé; Pregnancy; spermie; Male; Retrospective Studies; Female